GAMBARAN KADAR HEMOGLOBIN DAN BESI SERUM PADA WANITA HAMIL TRIMESTER 3 - Hasibuan, Angie Auryll Gracia; Berhimpon, Siemona; Rambert, Galdy Inri (JURNAL KEPERAWATAN, 2025)
ABSTRACT/ABSTRAK Background: Pregnant women, especially in the third trimester of pregnancy, are susceptible to various disorders, in particular iron deficiency anemia. Iron deficiency anemia is a serious global health issue, especially for pregnant women due to increased hemoglobin and serum iron requirements. In Indonesia, the prevalence of anemia among pregnant women is still a public health challenge that requires serious attention.. Aim: To determine the description of hemoglobin and serum iron (SI) as well as the prevalence of anemia in pregnant women in the 3rd trimester in Manado City. Method: Descriptive design with a cross-sectional approach. A total of 30 pregnant women in 3rd trimester were taken using purposive sampling. Data was obtained through laboratory examination of Hb and SI levels and interviews. Results: As many as 36.7% of respondents had normal Hb levels (≥12 g/dL), while 63.3% had low Hb levels (<12 g/dL). For serum iron levels, 66.7% were in the normal range (55-165 mg/dL), and 33.3% had low serum iron levels (<55 mg/dL). The prevalence of iron deficiency anemia was 26.7%. Conclusion: In the majority of respondents, hemoglobin levels were low and iron levels were normal. Most respondents did not experience iron deficiency anemia. Key Words: Hemoglobin; Serum Iron; 3rd Trimester Pregnant Women; Iron Deficiency Anemia.